Arbuscular Mycorrhizal Fungi and Dry Raw Garlic Stalk Amendment Alleviate Continuous Monocropping Growth and Photosynthetic Declines in Eggplant by Bolstering Its Antioxidant System and Accumulation of Osmolytes and Secondary Metabolites - Ghani, Muhammad Imran; Ali, Ahmad; Atif, Muhammad Jawaad; Ali, Muhammad; Amin, Bakht; Cheng, Zhihui (Frontiers in Plant Science, 2022)
Vegetable production under plastic sheds severely threatens regional eco-sustainability via anthropogenic activities (excessive use of agrochemicals, pesticides) and problems associated with replanting. Long-term successive cropping across growing seasons induces continuous cropping stress, whose effects manifest as diminished plant growth. Therefore, it is imperative that we develop environmentally sustainable approaches, such as replacing agrochemicals with vegetable waste like dry raw garlic stalk (DRGS) or use biofertilizers like arbuscular mycorrhizal fungi (AMF) (e.g., Diversispora epigaea). In this study, the influence of AMF on the growth, biochemical attributes, antioxidant defense system, phytohormones, accumulation of osmolytes, phenols, and mineral elements in eggplant grown on DRGS-amended soils under continuous monocropping (CMC) was studied. The results showed that inoculation with AMF or the DRGS amendment could improve the pigments’ content, photosynthesis, and antioxidant defense system; augmented phytohormones synthesis (except for ABA), and increased the leaves’ mineral nutrients. These parameters were enhanced most by the combined application of AMF and DRGS, which also increased the concentration of osmolytes, including proline, sugars, and free amino acids in eggplant when compared with the control. Furthermore, either AMF and DRGS alone, or in combination, ameliorated the induced stress from continuous cropping by reducing the incidence of Fusarium wilt and production of ROS (reactive oxygen species); lipid peroxidation underwent maximal reduction in plants grown under the combined treatments. The AMF, DRGS, and AMF + DRGS exhibited a lower disease severity index (33.46, 36.42, and 43.01%), respectively, over control. Hence, inoculation with AMF coupled with DRGS amendment alters the photosynthetic attributes in eggplant through the upregulation of its antioxidant system and greater accumulation of osmolytes, which led to the improved growth and yield of eggplant.